Odpowiedź :
Odpowiedź:
R)
3 * (2x + 1) = 10x - 0.6
6x + 3 = 10x - 0,6
6x - 10x = -0,6 - 3
-4x = -3,6 /:(-4)
x = 0,9
t)
6 * (0.2 + 0.02x) = 0.15 * (6+x)
1,2 + 0,12x = 0,9 + 0,15x
0,12x - 0,15x = 0,9 - 1,2
-0,03x = -0,3 /:(-0,03)
x = 10
t)
2/3 * (n + 3) - 3/7(n + 4) = 1
2/3n + 2 - 3/7n - 12/7 = 1
14/21n = 1 - 2 + 1 5/7 /*21/14
n = 5/7 * 21/14 = 15/14 = 1 1/14
Szczegółowe wyjaśnienie:
Odpowiedź:
r) 3*(2x+1)=10x-0,6
6x+3=10x-0,6
6x-10x=-0,6-3
-4x=-2,4 /:(-4)
x=0,6
t)
6*(0,2+0,02x)=0,15*(6+x)
1,2+0,12x=0,9+0,15x
0,12x-0,15x=0,9-1,2
-0.03x=-0,3 /:(-0,03)
x=10
t)
2/3(n+3)-3/7(n+4)=1
2/3n+2-3/7n-12/7=1
14/21n-9/21n=1-2+12/7
23/21n=-1+1 5/7
23/21n=5/7 /*21/23
n=5/7*21/23
n=15/23
Szczegółowe wyjaśnienie: